"With gentleness and respect" Pauline and Petrine studies in honor of Troy W. Martin - Mason, Eric Farrel 1969-; Whitters, Mark F. (Peeters, 2020)
This volume honors Troy W. Martin and his thirty years of fruitful scholarship in New Testament and related disciplines. Sixteen studies by an international group of scholars explore texts and themes prominent in Martin's own research in the Pauline letters and 1 Peter. Two articles consider rhetorical criticism of Galatians (David E. Aune, A. Andrew Das); four examine key passages and themes in Romans (Laurie J. Braaten, P. Richard Choi, Charles H. Cosgrove, and Mark F. Whitters); five explore issues of interpretation and reception of other Pauline texts (Christopher Forbes, George Lyons, Clare K. Rothschild, Todd D. Still, D. Francois Tolmie); and five address exegetical and rhetorical matters in 1 Peter (Jenny L. DeVivo, Eric F. Mason, Nancy Pardee, Russell B. Sisson, Duane F. Watson). The volume also includes a biographical tribute (Avis Clendenen and Jenny L. DeVivo), an annotated bibliography of Martin's academic publications (Teresa J. Calpino), and indices (compiled by Najeeb T. Haddad)."
Keywords: Bibel -- Paulinische Briefe; Bibel -- Petrusbrief -- 1.; Biblische Theologie; Bible / Epistles of Paul / Criticism, interpretation, etc; Bible / Peter / Criticism, interpretation, etc; Bible / Epistles of Paul; Bible / Peter; Criticism, interpretation, etc; Festschrift